Effect of Polyvinyl Alcohol (PVA) Containing Artemether in Treatment of Cutaneous Leishmaniasis Caused by Leishmania major in BALB/c Mice - Ebrahimisadr, Parisa (Kowsar, 2014)
BACKGROUND: Polyvinyl alcohol (PVA) is one of the well-known polymers, which has been used in numerous biomedical applications because of its good biocompatibility. OBJECTIVES: Due to problems made by the therapeutics already used for leishmaniasis, the aim of this study was to evaluate the effect of PVA containing artemether in treating cutaneous leishmaniasis in BALB/c mice. MATERIALS AND METHODS: Aqueous solution of PVA was prepared by mixing with Double Distilled Water. After preparation of PVA, 4.33 mg of each drug (main drug artemether and control drug 14% glucantime) was added to 100 g of prepared PVA-honey solution. The solution was incubated at 37°C and the release of artemether was evaluated by measuring absorbance at 260 nm wave length. In this study for treatment of mice lesion, we used PVA containing artemether and glucantime and this method was compared with ointment treatment. RESULTS: Mean diameters of lesions in mice treated with artemether were smaller than the control group and the differences were significant (P < 0.05). The mean lesion size of mice treated with PVA containing artemether in comparison with the group treated with ointment of artemether were smaller and the differences were significant (P < 0.05). CONCLUSIONS: PVA containing artemether is a new method for treatment of cutaneous leishmaniasis and according to the obtained results, artemether is an appropriate and effective drug, especially when used with PVA as a lesion dressing; thus we suggest that this method can be applied for the treatment of cutaneous leishmaniasis.